PENYELESAIAN SENGKETA WANPRESTASI PADA PERJANJIAN SEWA MENYEWA PESAWAT ANTARA HELICE LEASING S. A. S DAN ATTERISSAGE S. A. S DENGAN PT. GARUDA INDONESA TBK SECARA ARBITRASE INTERNASIONAL: PENYELESAIAN SENGKETA WANPRESTASI PADA PERJANJIAN SEWA MENYEWA PESAWAT ANTARA HELICE LEASING S. A. S DAN ATTERISSAGE S. A. S DENGAN PT. GARUDA INDONESA TBK SECARA ARBITRASE INTERNASIONAL - Imas Rosidawati Wiradirja; Amanda; Eddy Setiawan; Muhammad Fauzan; Sugiarto; Nugraha Pranadita (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
International trade disputes have been successfully settled by the London Court of International Arbitration (LCIA), a component of the international arbitration system. The decision of a breach of contract dispute involving an aircraft leasing agreement between Helice Leasing S.A.S (Helice) and Atterissage S.A.S (Atterissage) with PT. Garuda Indonesia Tbk (GI), decided by the LCIA, reflects this. After concluding that GI had violated the agreement, the LCIA ordered it to pay Helice and Atterissage the past-due rent as well as the remaining rent. Analysing the international arbitration procedure for resolving disputes and the award's enforcement is the goal of this research. Using a normative legal methodology, the study analyses case studies and legislation. The results show that arbitration uses a multi-step procedure to resolve disputes, including hearings, mediation or conciliation, the selection of an arbitration panel, the presentation of the parties' arguments and supporting documentation, and the arbitrator's ruling. The LCIA effectively resolved the disagreement, demonstrating the efficacy and efficiency of this approach. The enforcement of the award is permitted in Indonesia under Article 65 and Article 66 of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution (AAPS Law), provided that the Central Jakarta District Court has recognised the arbitration award and it does not contravene public order.